Impact of Cover Crops and Phosphorus Fertilizer Management on Nutrient Cycling in No-Tillage Corn-Soybean Rotation - R. E. Carver; N. O. Nelson; D. S. Abel; K. Roozeboom; G. J. Kluitenberg; P. J. Tomlinson; J. R. Williams (Kansas Agricultural Experiment Station Research Reports, 2017)
The objective of this study was to quantify the effects of cover crops and different fertilizer management techniques on the amount of nutrients being removed and recycled in the soil system. This study was conducted at Ashland Bottoms, KS, from 2014-2016. A 2 × 3 factorial design with three replicates was utilized in this study. The fertilizer management treatments included a control of 0 lb/a P2O5, along with fall broadcast and spring injected applications of P2O5based on a build and maintain recommendation system. Results show that total uptake of K2O and recycling of P2O5and K2O are directly influenced by cover cropping. Application of P2O5fertilizer also statistically impacted the yield of soybeans during the 2016 growing season.
Keywords: cover crop; phosphorus; nutrient uptake